(untitled) (Tzintzun, Revista de Estudios Históricos, 2022)
The projection of a country’s culture abroad is a characteristic action of what is called cultural diplomacy; many countries have used cultural diplomacy strategies to promote their identity, values, symbols, traditions, lifestyles, as well as the most outstanding artistic manifestations to position it as an admirable country, in such a way as to generate a favorable climate for cooperation and business with countries which maintains relations. The purpose of this article is to investigate the relevant milestones of Mexico’s cultural diplomacy throughout the 20th century. Thus, taking the Mexican case as an example, we intend to show how the cultural component in foreign policy contributed to reaffirm the country’s international prestige.